2018
DOI: 10.1186/s12984-018-0456-x
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for activity recognition in ambulant children and adolescents with cerebral palsy

Abstract: BackgroundCerebral palsy (CP) is the most common physical disability among children (2.5 to 3.6 cases per 1000 live births). Inadequate physical activity (PA) is a major problem effecting the health and well-being of children with CP. Practical, yet accurate measures of PA are needed to evaluate the effectiveness of surgical and therapy-based interventions to increase PA. Accelerometer-based motion sensors have become the standard for objectively measuring PA in children and adolescents; however, current metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 40 publications
3
69
1
2
Order By: Relevance
“…In the recent years wearable sensor techniques have increasingly been used for detecting specific movements of interest, e.g. stereotypical movement patterns in epilepsies as well as for activity monitoring in neurological disorders [95] including the general population of CP [96,97]. However, no study was found specifically for dyskinetic CP.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…In the recent years wearable sensor techniques have increasingly been used for detecting specific movements of interest, e.g. stereotypical movement patterns in epilepsies as well as for activity monitoring in neurological disorders [95] including the general population of CP [96,97]. However, no study was found specifically for dyskinetic CP.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…More generally speaking, the present study is also limited from the algorithmic point of view, not taking yet into consideration the growing and promising area of Machine Learning and AI techniques to classify and assess movements and performance from sensors' readings. These are perspectives that of course deserve to be further studied, having already produced interesting results in the field (Ahmadi et al 2018;Hagenbuchner et al 2015;Trost et al 2016). The difficulty however is also related to the freedom of the performed movements, since the tasks of each exercise could be accomplished by different subjects in completely different ways, according to the nature and severity of each child's pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the physical activity was based on ActiGraph activity monitor measurements. The ActiGraph measurements for health-related research were also carried out in published findings [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Features that can be derived from the accelerometer have been also used to recognize the presence and severity of motor fluctuations in patients with Parkinson's disease [18]. It has been also used with measurements of physical activity to evaluate the effectiveness of surgical and therapy-based interventions in children with cerebral palsy or to derive diurnal rest-activity patterns from actigraphy in adolescents and to analyze associations with adiposity measures and cardiometabolic risk factors [19,20].…”
Section: Actigraph Activity Monitormentioning
confidence: 99%